An innovative analytical approach for predicting the fundamental time period of moment-resisting frames (Fracture and Structural Integrity, 2025)
Most seismic design codes provide formulas for estimating base shear and lateral loads. To determine lateral loads, the building's fundamental vibration period must be calculated, either theoretically or experimentally. However, there is no simplified equation that accurately calculates this parameter. This paper proposes a new simplified formula for computing the fundamental period of reinforced concrete moment-resisting frames (MRFs). The proposed formula is validated through eigenvalue analysis of the mathematical models of various building frames using finite element methods (FEM), with varying structural properties along their height. The proposed model achieved an average prediction error of around 4% and an R² (coefficient of determination) value of 0.999 when compared to FEM results, outperforming existing empirical formulas. A sensitivity analysis was conducted to identify the effect of each of the design parameters, accompanied by a comparative evaluation against some formulas from the literature. The novelty of the suggested method is that it can calculate the fundamental period more accurately and easily by considering the stiffness and seismic mass of the building.
Keywords: . Reinforced-Concrete Frame MRF; Equivalent Stiffness; Equivalent Lumped Mass; Fundamental Vibration Period; Dynamic Analysis; Sensitivity Analysis